PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI HUBUNGAN MAKANAN DAN KESEHATAN - Oktaviani, Nurjamilah; Sujana, Atep; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2017)
Creative thinking skills used to solve the real problems in students life. However, in the reality this skill in not used as a goals in the learning process at school. So that, the students’ creative thinking skills are low. Aim softh is research is to find out the students’ creative thinking skills in high, moderate, and low ranks by using problem based learning. The research method used is Pre-Experimental with one group pre-testa and posttest designs. The samples are five grade students of SDN Babakan 01 and SDN Rancaheulang. The instruments used are creative thingking skills test, questionnaire, observation paper and interview. The learning process which is conducted in all three groups are able to increase creative thinking skills, is showed from the stattistic test result that Problem Based Learning is able to increase creative thinking skills significantly. Moreover, obtained the difference of increase in all three groups. The group which reach the best result among all three groups is the students group in high rank.